Hereditary neuralgic amyotrophy associated with a relapsing multifocal sensory neuropathy. - Thomas, P K (1993)
A family with neuralgic amyotrophy (idiopathic brachial plexus neuropathy) associated with a multifocal sensory neuropathy is described. Four members over two generations were affected by neuralgic amyotrophy, inherited as an apparent autosomal dominant trait; two also had a multifocal relapsing sensory neuropathy with the clinical features of Wartenberg's migrant neuropathy.